Zarządzanie długiem publicznym w USA - wybrane problemy - Babczuk, Arkadiusz (Public debt management in the U.S. - selected problems, 2006)
The subject of the following article is to present the most significant changes in the field of issuing procedures for American T reasury Securities over the period ofthe past 15 years. The changes concerned the rules of auctions o f marketable treasury securities. As a result of the analysis of contemporary studies as well as experiments carried out by American public debt managers, the auction procedures has changed from multiple-price sealed bid auction into uniform-price sealed bid auction. The above mentioned changes are aimed at the reduction of U.S. public debt costs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 256-265